PERCEPTION OF SMALL FARMERS IN SERBIA REGARDING THE USE OF ICT AND POSSIBILITIES OF ORGANIC AGRICULTURE - Ilic-Kosanovic, Tatjana; Pazun, Brankica; Langovic, Zlatko; Tomic, Srdjan (Economics of Agriculture, 2019)
During the last two decades there is a growing awareness of the importance of introducing organic agricultural production in Serbia due to issues of health, environmental protection and need for more sustainable agriculture. There is a need for education of small farmers on the possibilities of organic production and significance of information technologies for education, production and marketing. This paper aims to examine the perception on the possibilities of organic production and ICT use concerning their level of education. The study has included 143 farmers from Raška district, municipality Kraljevo. The statistical ANOVA analysis has been done by using the software package SPSS18 to explore an impact the education has on the perception of small farmers on the use of information technologies in education, production, and marketing of agricultural products. The results show statistically significant difference in the perception of small farmers on the usage of information technologies regarding their level of education.